Stories that banks tell: Narrative semiotics and the discourse of financial crisis - Marsen, Sky (Public Journal of Semiotics, 2025)
This paper combines a narrative-semiotic method and crisis communication theory to analyse the CEO and Chairperson’s letters in annual reports of international banks during the Global Financial Crisis of 2008. Its objective is to outline and apply narrative semiotics in identifying discursive patterns in banking strategies aimed at managing the crisis and addressing hostile audiences. As a benchmark to the narratives created in the annual reports, the paper examines reports of independent investigations to identify areas of agreement and dissent. Findings include a conflicting role attributed to regulation and bonus pay schemes between the narratives of banks and the narrative of the independent reports, a difference in tone in banks from different regions, and a prominent bolstering strategy across all banks. The paper’s significance lies in showing the value and relevance of narrative semiotics for crisis communication theory, a hitherto largely unexplored field.